Geohazard features of the Ligurian Sea - Danilo Morelli; Sébastien Migeon; Michele Locatelli; Paola Cianfarra; Laura Crispini; Nicola Corradi; Alessandra Savini; Ileana Balduzzi; Marianne Coste; Angela Cuppari; Enrico Olivari; Francesco Falese (Journal of Maps)
We present the characterization of geohazard-related features of the Ligurian Sea with the map of its physiographic domains (1:250,000 scale) and five maps (1:100,000 scale) of the morphological and morpho-bathymetric elements. These were realized in the framework of the MaGIC (Marine Geohazard along Italian Coasts) project, promoted by the Italian Civil Protection Department. The characterization of submarine geohazards along continental margins, together with mapping of marine geological features are critical for the management of coastal risks. Multibeam bathymetric data combined with high-resolution 2D reflection seismic data, allowed to identify and map the main tectono-sedimentary features related to mass movements along the Ligurian continental margin. A dense grid of seismic profiles allowed to improve the comprehension of the margin structure as well as its recent tectonic activity providing new insights concerning mass wasting processes and active tectonics relationships to plan further, focalized investigations in areas of maximum risk.